Renal function during long-term therapy with rituximab in patients with systemic sclerosis - M. N. Starovoitova; O. V. Desinova; L. P. Ananyeva; O. A. Koneva; L. A. Garzanova; O. B. Ovsyannikova; R. U. Shayakhmetova (Современная ревматология, 2023)
In systemic sclersis (SSc), different types of renal involvement occur. Their severity can range from asymptomatic deterioration of renal function to life-threatening damage, which is a complex therapeutic problem. Rituximab (RTM) has been used in the treatment of SSc and other autoimmune diseases with promising results, but its effect on renal function has not been adequately studied.   Objective: to evaluate the renal function during complex therapy, including RTM, in patients with SSc over a long-term follow-up (at least 1 year).   Material and methods. The study included 90 patients with SSc who were examined at least twice – before and 1–3.5 years after initiation of RTM treatment. Renal function was assessed by glomerular filtration rate (GFR) calculated according to the CKD-EPI formula. The stages of chronic kidney disease (CKD), blood pressure, daily proteinuria, skin score, activity, and indicators of lung function – forced vital capacity and diffusing capacity of the lungs – were also determined.   Results and discussion. Against the background of complex therapy with RTM, there was a statistically significant decrease in GFR in the entire group of patients at the end of observation. On the other hand, renal function remained stable in the majority of patients with initially preserved GFR and there was a 25 % decrease – from 20 to 15 patients – in the number of patients with CKD. In more than half of the patients who initially had CKD, GFR increased (n = 11) or stabilized (n = 2) after therapy, and it decreased in a statistically insignificant manner in only 7 patients, whereas the development of a more advanced stage of CKD was observed in only 2 cases. The results of the treatment of 2 patients who had previously experienced scleroderma renal crisis (SRC) are reviewed in detail.   Conclusion. In this study, there was no significant effect of RTM treatment on GFR and grade of CKD. Most patients had stable renal function; patients with an initial low grade of CKD showed a tendency toward stabilization of renal function. A significant decrease in GFR during long-term therapy noted in the entire patient group appears to be explained by an increase in renal insufficiency in patients with initially severe scleroderma renal damage, particularly due to SRC. Further studies on the effects of RTM therapy on renal function in patients with SSc are needed.